Persepsi Masyarakat mengenai Pengaruh Pengembangan Wisata Pantai terhadap Lingkungan: Studi Kasus di Kabupaten Pinrang, Indonesia - Rivai, Andi Alamsyah; Wahyuni, Sri (Jurnal Pendidikan Teknologi Pertanian, 2024)
Beach tourism in Pinrang Regency continues to develop. This tourism development has impact on various aspects, one of which is the environmental aspect. This research aims to analyze public perceptions regarding the effect of beach tourism development on the environment in Pinrang Regency. Public perceptions data were collected through filling out questionnaires and direct interviews. Apart from that, secondary data collection from local stakeholders was also carried out. The questionnaire was first analyzed for validity and reliability before being used. The data collected was then analyzed descriptively. Public perceptions based on gender and education level were analyzed for differences using non-parametric tests (Kruskal-Wallis H). The results of this research showed that the development of beach tourism in Pinrang Regency did not have a bad effect on the environment based on public perceptions. There was a significant difference in men's and women's perceptions of air pollution variables (p<0.05). Apart from that, there were significant differences in public perceptions on the vandalism, air pollution, noise pollution, narrowing of public spaces, and damage to plants variables based on education level (p<0.05). It is hoped that the results of this research will provide information for stakeholders in managing beach tourism better and improving the welfare of the surrounding community, especially in Pinrang Regency